Mythologizing Identity and History: A Look at the Celtic Past of Galicia - (:unkn) unknown (My University, 2006)
Following in the tradition of nineteenth-century Galician historians, who claimed to establish links between Galicia and other alleged Celtic nations, the Xeración Nós maintained the legacy of Celtic ancestry by importing and translating Irish literature. The most important translation for affirming the alleged Celtic identity of Xeración Nós was a selection of chapters from the Irish text Leabhar Gabhála(Book of Invasions). This article will provide a general overview of the historical works which established Galicia's Celtic ancestry. It will also consider why intellectuals chose to translate an Irish myth. By examining these issues, I will demonstrate how this text was influential in the Xeración Nós' agenda of enhancing the Galician language as well as establishing an alleged Celtic identity and a filial relationship with the Irish.
Keywords: Celticism; Rexurdimento; Vicetto; Murguía; Xeración Nós; Risco; Otero Pedrayo; Leabhar Gabhála